Seed Dispersal Distances by Ants Increase in Response to Anthropogenic Disturbances in Australian Roadside Environments - Palfi, Zsofia; Spooner, Peter G.; Robinson, Wayne (Frontiers in Ecology and Evolution, 2017)
Ants provide a common dispersal vector for a variety of plants in many environments through a process known as myrmecochory. The efficacy of this dispersal mechanism can largely determine the ability of species to track changes in habitat availability caused by ongoing land-use and associated disturbances, and can be critical for population gene flow and persistence. Field studies were conducted in a typical fragmented agricultural landscape in southern NSW, Australia, to investigate the extent to which dispersal services by ants are influenced by anthropogenic disturbances associated with roadwork activities (i.e. soil disturbance as the result of grading of roads). Observational experiments were performed in road segments that were divided into disturbed and non-disturbed zones, where Acacia pycnantha seeds were offered at multiple bait stations and monitored. For combined species, the mean dispersal distance recorded in the disturbed zone (12.2m) was almost double that recorded in the non-disturbed zone (5.4m) for all roadside sites. Our findings show that myrmecochory is an unevenly diffuse mutualism, where few ant species contributed to much of the dispersal of seeds. Iridomyrmex purpureus was responsible for all seed dispersal distances > 17m, where a maximum of 120m in disturbed, versus 69m in non-disturbed zones, was recorded. Rhytidoponera metallica and Melophorus bruneus were important seed dispersers in non-disturbed and disturbed zones, respectively. In general, large bodied ants tended to move more seeds to longer distances in disturbed zones, as opposed to non-disturbed zones, where smaller bodied species carried out a greater percentage of short distance dispersals (< 1m). We also recorded secondary dispersal events from nests by I. purpureus, a phenomenon previously not quantified. Infrequent, long distance dispersal to suitable sites may be highly important for seedling recruitment in disturbed or modified habitats in otherwise highly fragmented rural environments.